2022
DOI: 10.1038/s41598-022-22194-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of circulating small extracellular vesicle-derived miRNAs as diagnostic biomarkers for differentiating between different pathological types of early lung cancer

Abstract: Lung cancer is the leading cause of cancer-related death worldwide. MicroRNAs (miRNAs) in circulating small extracellular vesicles (sEVs) have been suggested to be potential biomarkers for cancer diagnosis. The present study was designed to explore whether plasma-derived sEV miRNAs could be utilized as diagnostic biomarkers for differentiating between early-stage small cell lung cancer (SCLC) and early-stage non-small cell lung cancer (NSCLC). We compared the miRNA profiles of plasma-derived sEVs from healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Sozzi et al., reported that a combination of both plasma miRNA signature and LDCT resulted in the reduction of LDCT false-positive rate ( 16 ), highlighting the utility of miRNA in informing lung cancer diagnoses. Despite investigation describing miRNAs deregulation in lung cancers ( 17 ), few studies have identified a panel of miRNAs distinguishing SCLC from NSCLC ( 12 , 18 ). NSCLC represents the majority of lung cancer cases while SCLC remains a less common subtype of tumor that is often not considered in biomarker studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sozzi et al., reported that a combination of both plasma miRNA signature and LDCT resulted in the reduction of LDCT false-positive rate ( 16 ), highlighting the utility of miRNA in informing lung cancer diagnoses. Despite investigation describing miRNAs deregulation in lung cancers ( 17 ), few studies have identified a panel of miRNAs distinguishing SCLC from NSCLC ( 12 , 18 ). NSCLC represents the majority of lung cancer cases while SCLC remains a less common subtype of tumor that is often not considered in biomarker studies.…”
Section: Discussionmentioning
confidence: 99%
“…Four specific miRNAs (Let-7b-3p, miR-150-3p, miR-145-3p, and miR-139-3p) were identified in the plasma of cancer patients, suggesting their potential role as biomarkers for CRC diagnosis [ 21 ]. In early lung cancer detection, miRNA profiles were analyzed using plasma-derived sEVs from healthy controls, patients with small cell lung cancer (SCLC), and patients with non-small cell lung cancer (NSCLC) [ 22 ]. miRNA-483-3p showed potential as an early diagnostic biomarker for SCLC, while miRNA-152-3p and miRNA-1277-5p were identified as early diagnostic biomarkers for NSCLC [ 22 ].…”
Section: Sevs As Cancer Biomarkersmentioning
confidence: 99%
“…In early lung cancer detection, miRNA profiles were analyzed using plasma-derived sEVs from healthy controls, patients with small cell lung cancer (SCLC), and patients with non-small cell lung cancer (NSCLC) [ 22 ]. miRNA-483-3p showed potential as an early diagnostic biomarker for SCLC, while miRNA-152-3p and miRNA-1277-5p were identified as early diagnostic biomarkers for NSCLC [ 22 ]. Nasopharyngeal carcinoma (NPC) is usually diagnosed at a late stage and consequently shows a poor prognosis after treatment [ 23 ].…”
Section: Sevs As Cancer Biomarkersmentioning
confidence: 99%
“…Furthermore, multiple studies on EV-based diagnosis of cancer have suggested that EV transcriptomic and proteomic biomarkers can increase the likelihood of early and sensitive detections of cancer. For example, plasma EV-derived miRNA-483-3 could be used as a potential biomarker for the diagnosis of early-stage small cell lung cancer, and miRNA-152-3p and miRNA-1277-5p could be used for the diagnosis of early-stage non-small cell lung cancer [ 18 ]. Glypican 1 (GCP1) and macrophage migration inhibitory factor (MIF) were identified as potential exosome-associated biomarkers for early diagnosis of pancreatic cancer [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%